Effects of fiber density and plasma modification of nanofibrous membranes on the adhesion and growth of HaCaT keratinocytes. (January 2015) - Bacakova, Marketa; Lopot, Frantisek; Hadraba, Daniel; Varga, Marian; Zaloudkova, Margit; Stranska, Denisa; Suchy, Tomas; Bacakova, Lucie
It may be possible to regulate the cell colonization of biodegradable polymer nanofibrous membranes by plasma treatment and by the density of the fibers. To test this hypothesis, nanofibrous membranes of different fiber densities were treated by oxygen plasma with a range of plasma power and exposure times. Scanning electron microscopy and mechanical tests showed significant modification of nanofibers after plasma treatment. The intensity of the fiber modification increased with plasma power and exposure time. The exposure time seemed to have a stronger effect on modifying the fiber. The mechanical behavior of the membranes was influenced by the plasma treatment, the fiber density, and their dry or wet state. Plasma treatment increased the membrane stiffness; however, the membranes became more brittle. Wet membranes displayed significantly lower stiffness than dry membranes. X-ray photoelectron spectroscopy (XPS) analysis showed a slight increase in oxygen-containing groups on the membrane surface after plasma treatment. Plasma treatment enhanced the adhesion and growth of HaCaT keratinocytes on nanofibrous membranes. The cells adhered and grew preferentially on membranes of lower fiber densities, probably due to the larger area of void spaces between the fibers.